Anti-Leukemic Properties of Histamine in Monocytic Leukemia: The Role of NOX2 - Kiffin, Roberta; Grauers Wiktorin, Hanna; Nilsson, Malin S.; Aurelius, Johan; Aydin, Ebru; Lenox, Brianna; Nilsson, Jonas A.; Ståhlberg, Anders; Thorén, Fredrik B.; Hellstrand, Kristoffer; Martner, Anna (Frontiers in Oncology, 2018)
In patients with acute myeloid leukemia (AML), treatment with histamine dihydrochloride (HDC) and low-dose IL-2 (HDC/IL-2) in the post-chemotherapy phase has been shown to reduce the incidence of leukemic relapse. The clinical benefit of HDC/IL-2 is pronounced in monocytic forms of AML where the leukemic cells express histamine type 2 receptors (H2R) and the NAPDH oxidase-2 (NOX2). HDC ligates to H2Rs to inhibit NOX2-derived formation of reactive oxygen species, but details regarding the anti-leukemic actions of HDC remain to be elucidated. Here we report that human NOX2+ myelomonocytic/monocytic AML cell lines showed increased expression of maturation markers along with reduced leukemic cell proliferation after exposure to HDC in vitro. These effects of HDC were absent in corresponding leukemic cells genetically depleted of NOX2 (NOX2-/-). We also observed that exposure to HDC altered the expression of genes involved in differentiation and cell cycle progression in AML cells and that these effects required the presence of NOX2. HDC promoted the differentiation also of primary monocytic, but not non-monocytic, AML cells in vitro. In a xenograft model, immunodeficient NOG mice were inoculated with wild-type or NOX2-/- human monocytic AML cells and treated with HDC in vivo. The administration of HDC reduced the in vivo expansion of NOX2+/+ but not of NOX2-/- human monocytic AML cells. We propose that NOX2 may be a conceivable target in the treatment of monocytic AML.